Mengoptimalkan kreativitas pendidik paud melalui kegiatan gugus - Wahyuningsih Wahyuningsih (Universitas Sebelas Maret, 2021)
Early childhood is a golden period for child development to acquire an educationalprocess. Children are entrusted by God that we must take care of and educate us to become useful human beings. Children have the right and opportunity to develop, especially in the field of education. As a golden method, the child's brain will develop rapidly. Early childhood education is very important for the survival of the nation and really needs serious attention from the government. The early childhoodcluster is very useful for early childhood educators to increase the creativity of early childhood educators. Activities carried out in the early childhoodcluster are in the form of developing the quality of teachers according to their competencies, cooperating with the business world and the community that cares for early childhood education, conducting surveillance programs, increasing community participation, developing cluster innovations.